2002
DOI: 10.1007/s11745-002-0981-4
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoproteins A‐I and A‐II downregulate neutrophil functions

Abstract: This work reports the effect of the apolipoproteins A-I and A-II (apoA-I and apoA-II) on the release of tumor necrosis factor (TNF)-alpha, interleukin (IL)-1beta, IL-8, and IL-1 receptor antagonist (IL-1Ra) and on the oxidative burst of human neutrophils. By themselves, apoA-I and apoA-II do not affect the basal liberation of these cytokines, whereas apoA-I affects the release of IL-1beta from lipopolysaccharide (LPS)-stimulated neutrophils and apoA-II affects IL-8 released from LPS-stimulated neutrophils. Apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 20 publications
1
47
0
1
Order By: Relevance
“…580 Moreover, in proteins eluted from TREATED N surfaces -onto 581 which many neutrophils adhered during blood exposure -highest 582 quantities of plasminogen were found, while significantly lower 583 amounts of apolipoprotein A and a2-macroglobulin were detected. 584 Previous findings suggested that a2-macroglobulin inhibits leuko-585 cyte adhesion to biomaterials surfaces [39], and apolipoprotein A 586 reduces neutrophil recruitment and function [40][41][42], while plas-587 minogen recruits neutrophils [43]. We conclude that the 588 TREATED N surfaces were therefore covered with less neutrophil …”
mentioning
confidence: 70%
See 1 more Smart Citation
“…580 Moreover, in proteins eluted from TREATED N surfaces -onto 581 which many neutrophils adhered during blood exposure -highest 582 quantities of plasminogen were found, while significantly lower 583 amounts of apolipoprotein A and a2-macroglobulin were detected. 584 Previous findings suggested that a2-macroglobulin inhibits leuko-585 cyte adhesion to biomaterials surfaces [39], and apolipoprotein A 586 reduces neutrophil recruitment and function [40][41][42], while plas-587 minogen recruits neutrophils [43]. We conclude that the 588 TREATED N surfaces were therefore covered with less neutrophil …”
mentioning
confidence: 70%
“…Surface-specific blood reactions were confirmed by scanning electron micro- 41 scopy and the adsorbed protein layers were characterized by mass spectrometry. This powerful 42 proteomics tool allowed the identification and quantification of over hundred surface-adhering proteins. 43 Proteins associated with the coagulation cascade, platelet adhesion and neutrophil function correlated 44 with the various blood surface activations observed.…”
mentioning
confidence: 99%
“…In vitro, SAA induces the expression and release of proinflammatory cytokines such as tumor necrosis factor-alpha (TNF-␣), interleukin 1beta (IL-1␤) and the chemokine interleukin-8 (IL-8) in neutrophils and monocytes [2][3][4][5]. Furthermore, SAA acts as a priming agent, rendering the neutrophils more responsive to opsonized particles [6].…”
Section: Introductionmentioning
confidence: 99%
“…Functional assays and flow cytometry analyses show that apoA-I inhibits contact-mediated activation of monocytes by binding to stimulated T cells, thus inhibiting TNF-a-and IL-1h-production [21]. Furthermore, apoA-I downregulates neutrophile function [22], and inhibits monocyte inflammatory functions in peripheral blood monocytes activated by either specific antigens or lectins without affecting cell proliferation [21].…”
Section: Introductionmentioning
confidence: 99%